The Effect of Interactive Learning Application on Students’ Performance in Analyzing World War I Events - Narag, Lloyd Ryan (International Journal of Arts, Sciences and Education, 2021)
Borderless 21st century learning means helping the learners meet higher performance in-class and national examinations through the use of interactive ICT inspired teaching aids. With these considerations, the teacher-researcher created the Interactive Learning Application as a means of helping students improve their performance in Araling Panlipunan. The students of Grade 8-Copper and Grade 8-Antimony, A.Y. 2019-2020, stood as the respondents of the study. The groups were randomly selected to systematically assign them as the Control Group and Experimental Group. The results revealed that in the pretest, scores of the control group were more consistent compared to the experimental group. However, after the use of the intervention, the posttest scores of the experimental group appeared to be more consistent. Moreover, in the pretest mean scores of both groups showed no significant difference; this suggests that both groups are of the same level in terms of their performance in analyzing World War I events. Finally, the posttest scores of both groups showed significant difference. It can be deduced from the study that the use of the Interactive Learning Application is effective in improving students’ performance in examining the events of World War I. Further, it is recommended for use in Araling Panlipunan classes with the same topic.